Primary and Secondary Nutrients-a Boon to Defense System against Plant Diseases - Bhaduri, Debarati; Rakshit, Rajiv; Chakraborty, K. (International Journal of Bio-resource and Stress Management, 2023)
Plant diseases are one of the major limiting factors to shrink agricultural production and farmers use high amounts of toxic chemicals to control plant diseases, unaware of the fact that balanced nutrition can check diseases to an extent. Plant nutrients may affect disease susceptibility through plant metabolic changes, thereby creating a more favorable environment for disease development. When a pathogen infects a plant, it alters the plant’s physiology, particularly with regard to mineral nutrient uptake, assimilation, translocation, and utilization. They may also interfere with translocation or utilization of nutrients, inducing nutrient deficiencies or toxicities. The resulting deficiencies may lead to secondary infections by other pathogens. Ionomics, emerged as the study of the ionome (mineral nutrient and trace element composition representing inorganic component of cell), depends on the growth, physiology and genetic modifications of the plant cells. Nutrients are essential for the metabolism of crop plants hence growth and yield as well as can be considered as an important component in plant-disease interactions. Because of the complex interaction between disease, nutrient and environment, vivid information is required about how a particular nutrient is actually working in crop plants to develop a strong defense system. Knowledge on plant nutrition thus deserves a priority for disease management as a part of integrated crop production system, because balanced nutrient supply ensures optimal plant growth and is usually considered optimal for disease resistance as well. Thus, this article focuses on the information regarding management of plant diseases (fungal, bacterial and viral) by balanced application of nutrients with a special emphasis to primary (N, P, K) and secondary (Ca, Mg, S) nutrients.